Perception of Players towards National Sports Council - Shrestha, Madhav Kumar; Karki, Sarala (JMC Research Journal, 2018)
This study entitled “Perception of players towards National Sports Council", aimed to find out the perception of players towards National Sports Council, and to describe and analyze the perception of players towards National Sports Council. The necessary information was taken from different players and member of National Sports Council. Altogether, there were one hundred and fifty respondents selected from different games and members of National Sports Council. The main source of data was primary. The researchers used ready-made tools made by Carr, where eleven statements were involved to gather data. There were diverse perceptions towards games and sports in Nepal. Among 150 respondents 56 (37.3 %) expressed strongly disagree, 83 (55.3%) disagree, 02 (01.3%) undecided, 6 (4 %), agree and 3 (2 %) strongly agree on the statement “National Sports Council manage proper training and coaching program for players.”